Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggan Kantor Pos Durenan Kabupaten Trenggalek - Dea Nurita Febriana; Moh. Gufron (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the effect of service quality and promotion on customer satisfaction at the Durenan POS Office, Trenggalek Regency. This research uses a quantitative approach with the population being visitors to the Durenan POS Office, Trenggalek Regency. The sampling method in the research was non-probability sampling, using accidental sampling of 100 respondents. Data was obtained through a questionnaire and analyzed using the SPSS application with multiple linear regression analysis. The research results show that partially service quality has a positive and significant effect on customer satisfaction with t count > t table (2.657 > 1.985) and a significance value of 0.009 < 0.05. Promotion has a positive and significant effect on customer satisfaction with t count > t table (16.210 > 1.985) and a significance value of 0.000 < 0.05. Meanwhile, simultaneously, service quality and promotion have a positive and significant effect on customer satisfaction with calculated f > f table (210.030 > 3.939) and a significance value of 0.000 < 005. The coefficient of determination shows 0.809. This shows that 80.9% of changes in customer satisfaction are influenced by service quality and promotions. Meanwhile, the remaining 19.1% is due to other variables outside those studied.